Right thoracotomy approach for open heart surgery - Mir, Ishtyak Ahmed; Ahangar, A. G. (International Journal of Research in Medical Sciences, 2017)
Background: Median sternotomy approach provides excellent exposure of all the chambers of heart for performing open heart surgery, but this approach is the most invasive used for any surgical procedure. Besides an ugly scar, median sternotomy not only increases the morbidity but at times mortality also. To have an acceptable postoperative scar and to avoid the morbidity and mortality associated with median sternotomy, the present study was conducted to find an alternative to median sternotomy in patients with atrial septal defect, mitral and tricuspid valve disease. Methods: Patients were positioned with right side elevated 30-45 degree, and heart was approached by right anterior thoracotomy, through 4th intercostals space. Pericardium was opened anterior to phrenic nerve, and upper end pericardial stay sutures given to get aorta more anterior. Aortic and bicaval cannulation was done and intracardiac procedures were performed as are done after standard median sternotomy. Results: Difficult aortic cannulation and fracture to costochondral junction was the problem observed in some patients. Repair of atrial septal defect was the most common operation performed. Sternotomy, rib resection and peripheral cannulation was not needed in any of these patients. Post-operative period was uneventful in majority. Conclusions: In all patients above 4 years of age, with normal aortic valve, without active lung disease / previous right thoracotomy, having isolated atrial septal defects, mitral and tricuspid valve disease the heart should be approached through right anterior thoracotomy.